Security Challenges and Protocols in the Expanding Realm of IoT: A Comprehensive Survey (International Journal of Engineering and Computer Science, 2024)
The Internet of Things (IoT) is rapidly growing and bringing innovation to various fields. However, this expansion comes with challenges, especially in terms of security. This survey focuses on IoT security and privacy, highlighting the need for strong protocols and standards. It explores security issues in interconnected devices, smart homes, and cities. The paper discusses current security situations, addressing problems like unauthorized access and data manipulation. It suggests solutions through sustainable standards. Despite the ongoing introduction of new smart devices, security concerns are often overlooked, posing risks for consumers and businesses. The paper concludes with a summary, laying the groundwork for future research to enhance IoT security protocols.